2018
DOI: 10.1002/rmb2.12086
|View full text |Cite
|
Sign up to set email alerts
|

Decreased carbonyl reductase 1 expression promotes tumor growth via epithelial mesenchymal transition in uterine cervical squamous cell carcinomas

Abstract: PurposeCarbonyl reductase 1 (CBR1) is involved in cancer progression. Recently, the authors reported that the loss of CBR1 expression is associated with a poor prognosis in uterine cervical cancer. Here, we investigated whether the decreased CBR1 expression promotes cancer progression by inducing the epithelial mesenchymal transition (EMT).MethodsAntisense constructs of CBR1 complementary DNA (antisense clones) and the empty vectors (control clones) were transfected into human uterine cervical squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Total protein were extracted and subjected to SDS-PAGE and then transferred to membrane as described previously 18,44 . The membranes were incubated for overnight with the following antibodies: C/EBPβ (Santa Cruz Biotechnology), HIF1α (Novus Biologicals, USA) and Histone H3 (Cell Signaling Technology, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Total protein were extracted and subjected to SDS-PAGE and then transferred to membrane as described previously 18,44 . The membranes were incubated for overnight with the following antibodies: C/EBPβ (Santa Cruz Biotechnology), HIF1α (Novus Biologicals, USA) and Histone H3 (Cell Signaling Technology, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Cervical cancer is the second most common malignant tumor in women worldwide, and the second most common cause of cancer-related death in women. [1,2] The International Federation of Obstetrics and Gynecology (FIGO) reported that although surgical techniques, radiotherapy equipment, and techniques have been greatly improved and developed, the survival rate of cervical cancer has not improved since 1950, and the overall 5-year survival rate keeps around 40%. [3] There are 2 clinical variants including cervical squamous cell carcinomas (CSCC) occupying 85% to 90% and adenocarcinoma carcinomas comprising 10% to 15% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…CBR1 is present in a variety of organs including liver, kidney, breast, ovary, and vascular endothelial cells, and its primary function is considered to control fatty acid metabolism (15). Interestingly, CBR1 has been reported to regulate malignant behaviors of cancer cells: Decreasing the expression of CBR1 induced cell proliferation and tumorigenesis in vitro and in vivo experiments accompanied by a decreased expression of E-cadherin, and activated matrix metalloproteinases (MMPs) in ovarian, uterine cervical, or uterine endometrial cancers (16–21). This suggests that the decreased expression of CBR1 promotes tumor growth and invasion activities.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanism of EMT, transforming growth factor (TGF)-β, which has roles in cell proliferation, differentiation, and tumorigenesis, has been reported to be closely associated with EMT in many epithelial and mesenchymal tumors (34,35). We previously analyzed pathways that are regulated by CBR1 in a uterine cervical cancer cell line overexpressing CBR1 (21). Of 15 pathways that were analyzed, the TGF-β signaling pathway was found to be the most important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation